Estudo da utilização de cinza de casca de arroz e efluente de biogás na plasticidade de materiais cerâmicos - Silva, Bruna Pereira da (2017)
The study analyzed the importance of seeking technologies for sustainable development in the field of red ceramic products. The plasticity characteristics of three types of soils, dystroferric Red Latosol, kaolinite and bentonite were evaluated when tested with water and with condensed gas (biogas effluent). Composites were made, and the Latosol was considered as the matrix and the additions of kaolinite, bentonite and rice husk ash as reinforcements. The methodology used followed the prerogatives of ABNT standards, NBR 6459, to determine the liquidity limit. The main focus of the analysis was the variation in the plasticity range of the composites when the molding fluid changes from water to condensed gas. The results showed that the Red Latosol in natura does not present a high plasticity, suggesting the incorporation of additives, whereas kaolinite and bentonite in natura have high plasticity. The incorporation of the reinforcements increased the plasticity of the matrix, and the kaolinite implied a smaller increase of plasticity and the bentonite in a larger increase. It was also observed that the use of condensed gas in substitution of water resulted in an improvement of the plastic characteristics of the matrix, suggesting its use in the manufacture of ceramic pieces. The contribution of this study is the reduction of the use of natural resources and the substitution of water by an industrial residue, in the production of ceramic materials, as regards to the improvement of plasticity.